Distinct selectivity inside self-assembled coordination cages - Liang, Yang; Zhou, Xiaojuan; Gopi, Sreeraj; Wang, Rui (Frontiers in Chemistry, 2023)
Supramolecular containers have long been applied to regulate organic reactions with distinct selectivity, owing to its diverse functions, such as the ability to pose guest molecule(s) with certain orientation and conformation. In this review, we try to illustrate how self-assembled coordination cages could achieve this goal. Two representative cage hosts, namely self-assembled Pd(II)-ligand octahedral coordination cage ([Pd6L4]12+) and self-assembled Ga(III)-ligand tetrahedral coordination cage ([Ga4L6]12-), are selected as the pilot hosts, in which this mini review is divided. And representative works of this area are presented here in brief.